2021
DOI: 10.3390/jcdd8110153
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Tissue Engineering for the Treatment of Myocardial Infarction

Abstract: Poor cell engraftment rate is one of the primary factors limiting the effectiveness of cell transfer therapy for cardiac repair. Recent studies have shown that the combination of cell-based therapy and tissue engineering technology can improve stem cell engraftment and promote the therapeutic effects of the treatment for myocardial infarction. This mini-review summarizes the recent progress in cardiac tissue engineering of cardiovascular cells from differentiated human pluripotent stem cells (PSCs), highlights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 108 publications
(164 reference statements)
0
7
0
Order By: Relevance
“…Long-term culture 12 , 13 , drug selection, metabolism 16 , 17 , mechanical stimulus 46 , 47 , tissue engineering 14 , 15 , electrical stimulus 48 , microRNA 49 , cell-cell interaction 15 , growth hormones 50 , 51 , and modulation of signaling pathways, such as mTOR 52 and WNT 53 , have been shown to more or less efficiently promote maturation of hPSC-CMs. In the current study, we showed that AA, which is also called vitamin C and is an essential nutrient, promoted MLC2v protein expression in hiPSC-CMs.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term culture 12 , 13 , drug selection, metabolism 16 , 17 , mechanical stimulus 46 , 47 , tissue engineering 14 , 15 , electrical stimulus 48 , microRNA 49 , cell-cell interaction 15 , growth hormones 50 , 51 , and modulation of signaling pathways, such as mTOR 52 and WNT 53 , have been shown to more or less efficiently promote maturation of hPSC-CMs. In the current study, we showed that AA, which is also called vitamin C and is an essential nutrient, promoted MLC2v protein expression in hiPSC-CMs.…”
Section: Discussionmentioning
confidence: 99%
“…(b) Tissue engineering: Techniques are developed to create viable cardiac tissue grafts from iPSCs, using biodegradable scaffolds that support cell growth and integration. These tissues can replace a damaged myocardium and incorporate features like electrical conductivity to boost functional integration [21,22]. (c) Genetic modifications: iPSCs are genetically modified to improve survival, proliferation, and differentiation.…”
Section: Induced Pluripotent Stem Cells (Ipscs)mentioning
confidence: 99%
“…Collagen, the most abundant structural protein in the body, is also one of the most common natural polymers used to engineer the heart [192][193][194]. Other natural polymers used to produce engineered heart include gelatin [195][196][197], alginate [198,199], chitosan [200,201], fibrin [202,203], silk [204][205][206], and decellularized matrices [159,207,208].…”
Section: Biomaterials In Cardiac Tissue Engineeringmentioning
confidence: 99%
“…Scaffolds, hydrogels Bioactivity, biocompatability, biodegradability, low toxicity, low cost [195][196][197] Alginate Scaffolds, hydrogels Biocompatability, biodegradability, non-adhesive, ease of modification, low toxicity, low cost [198,199] Chitosan Scaffolds, hydrogels Biocompatability, biodegradability, ease of modification, antimicrobial, low toxicity, low cost [200,201] Fibrin Scaffolds, hydrogels Bioactivity, biocompatability, biodegradability, ease of fabrication, low toxicity [202,203] Silk Scaffolds, hydrogels Bioactivity, biocompatibility, dynamic biodegradability, ease of modification, mechanical strength, low toxicity [204][205][206] ECM Scaffolds, hydrogels Bioactivity, biodegradability, endogenous integration, replication of complex native microenvironment [159,207,208] Polyethylene glycol (PEG)…”
Section: Gelatinmentioning
confidence: 99%